Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1159/000299838
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pre-Ejection Period during Prenatal Life

Abstract: Perinatal clinicians are confronted with the problem that they are supposed to gather information about the condition of the unborn child almost exclusively by monitoring the rate of the fetal heart. Human heart rate recording, however, is no more or less informative in utero than in the newborn nursery. Determination of the pre-ejection period (PEP) of the fetal heart might provide information regarding the performance of the heart of the human fetus in utero and about its cardiovascular adjustments during fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…A double monophasic PEP increase appears to be characteristic for cord complications; 89% of all fetuses in our material with heart rate changes during the contraction (N = 103) who had a twostep type PEP increase had a documented cord complication. This second rise in PEP following an initial rise has been observed by EVERS and DE HA AN [20,21] in chronic sheep experiments with poorly oxygenated fetal lambs (e.g., Figures 4 and 5). EVERS and DEHAAN [20,21] demonstrated that the second PEP rise is caused by a second increase in arterial blood pressure.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A double monophasic PEP increase appears to be characteristic for cord complications; 89% of all fetuses in our material with heart rate changes during the contraction (N = 103) who had a twostep type PEP increase had a documented cord complication. This second rise in PEP following an initial rise has been observed by EVERS and DE HA AN [20,21] in chronic sheep experiments with poorly oxygenated fetal lambs (e.g., Figures 4 and 5). EVERS and DEHAAN [20,21] demonstrated that the second PEP rise is caused by a second increase in arterial blood pressure.…”
Section: Discussionsupporting
confidence: 79%
“…This second rise in PEP following an initial rise has been observed by EVERS and DE HA AN [20,21] in chronic sheep experiments with poorly oxygenated fetal lambs (e.g., Figures 4 and 5). EVERS and DEHAAN [20,21] demonstrated that the second PEP rise is caused by a second increase in arterial blood pressure. If the ,alpha-adrenergic receptors in the fetal lamb were blocked with phentolamine the second rise in blood pressure and PEP was not observed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, obstruction of the umbilical cord had a more pronounced effect on fetal acid-base state. The effect of maternal common iliac artery occlusion on the fetal acidbase state was less striking, possibly due to the extended collateral circulation in the pelvis of the ewe, which often results in an incomplete and variable uteroplacental blood flow after occlusion [16]. In both experiments PaCCK increased significantly during obstruction and decreased within a few minutes after release of the clamp.…”
Section: Placental Embolizationmentioning
confidence: 80%
“…The fetal PEP was studied in the 1970s and 1980s as a possible parameter of fetal condition [5][6][7][8][9][10] . It was suggested that PEP reflects both myocardial contractility and the loading conditions of the heart, and may be a useful indicator of fetal cardiac performance and hence of the condition of the fetus as a whole [5] .…”
Section: Introductionmentioning
confidence: 99%